DIGITALISASI PEMETAAN UKM TENUN GARUT BERBASIS SISTEM INFORMASI GEOGRAFIS SEBAGAI MEDIA KOMUNIKASI DAN PEMASARAN PRODUK LOKAL - Sri Wulandari, Maria; Noveandini, Rahayu; ., Sutarno (Proceeding SENDI_U, 2015)
Garut has already been wellknown as ones of the silk producer area from its row materials up to artificial silk.But unfortunately there is no new generation studying and even not keeping continuously their Garutâs textileindustries. Garutâs textile industries are not to be able to compete with other popular textile industries where arealso enough wellknown like Sumbawa, Kalimantan, Bali, Sumatra and Sulawesi. The processing needs morelayer times,for examples one meter cloth needed moreless one week. So it causes the price of Garutâs textile ismore higher than other. Nowdays, the labour also creates more up date innovation specially for fashionproducts. The exclusive Gartutâs textile is geometrics style and by the big size flowers. To over come themarketing problem above here is the writer builds up an application for services informations by usingGeografis Information System based on web for giving more informations specially for the spreading UKMaround Garut area. The purpose of forming this application is for overcome the marketing problems and alsotaking port how to keep continuously and improving Garutâs creative textile industries. If itâs not done, therewill be hopless for the picture Garutâs textile and at last will be disappeared.Key words : Marketing, Keeping Life, Creatives industry, UKM, Geografis Information Systems